2023
DOI: 10.3390/v15020489
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Glecaprevir/Pibrentasvir-Induced Liver Injury and Efficacy of Ursodeoxycholic Acid

Abstract: Although glecaprevir/pibrentasvir (GP) therapy is recommended as a first-line treatment for hepatitis C virus (HCV) infection, serious drug-induced liver injury occasionally develops. The present study aimed to elucidate real-world risk factors for GP-induced liver injury and to evaluate the efficacy of add-on ursodeoxycholic acid (UDCA) for liver injury. We analyzed 236 HCV patients who received GP therapy. GP-induced liver injury was defined as any elevation to grade ≥1 in total bilirubin (TB), aspartate ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This has demonstrated a subsequent improvement in liver function tests within a matter of weeks [5][6][7]13]. One retrospective cohort study suggested the potential benefit of adding ursodeoxycholic acid to manage GP-induced liver injury while maintaining therapy, even with significant hyperbilirubinemia >2 [14].…”
Section: Discussionmentioning
confidence: 99%
“…This has demonstrated a subsequent improvement in liver function tests within a matter of weeks [5][6][7]13]. One retrospective cohort study suggested the potential benefit of adding ursodeoxycholic acid to manage GP-induced liver injury while maintaining therapy, even with significant hyperbilirubinemia >2 [14].…”
Section: Discussionmentioning
confidence: 99%